UJI AKTIVITAS TABIR SURYA PADA BEBERAPA SPESIES DARI FAMILY ZINGIBERACEAE DENGAN METODE SPEKTROFOTOMETRI - Fitriyanti Jumaetri Sami; Syamsu Nur; Megawati M. Martani (As-Syifaa Jurnal Farmasi, 2015)
Testing activity sun screen of several species from family Zingiberaceae with a spectrophotometric method have been. Study purpose is to obtain data on the sunscreen activity of ginger extract Z. officinale var. Officinale, Z. officinale var. Rubrum and Zingiber zerumbet SM and their combination with the parameters of % transmission of erythema, % transmission of pigmentation and SPF. The method used an experimental laboratory. Evaluation of the activity of ethanol extract of Z. officinale var. Officinale, Z. officinale var. Rubrum and Zingiber zerumbet SM made by maceration method using 70% ethanol. The test is based on the ability of the absorb the rays ultraviolet. Research carried out by the respective concentrations of ethanol extract of Z. officinale var. Officinale, Z. officinale var. Rubrum and Zingiber zerumbet SM of 200 ppm , 400 ppm , 600 ppm, 800 ppm and 1000 ppm. Based on percent transmission of erythema and percent transmission of pigmentation at a concentration of 1000 ppm, respectively ethanol extract Z. officinale var. Officinale, Z. officinale var . Rubrum and Zingiber zerumbet SM could be used as a sunscreen but still weak to be used as sunscreen ingredients. The result showed that combined Z. officinale var. Officinale, Z. officinale var. Rubrum and Zingiber zerumbet SM at a concentration of 500 ppm obtained percentage value of 1% transmission of erythema and 3,9% of pigmentatied transmission and categories as sunblock with SPF value is 50 protection.